Hybrid Graphene/Gold Plasmonic Fiber-Optic Biosensor - Zhang, Nancy Meng Ying (2017)
A 2D material/metal hybrid plasmonic sensor is demonstrated by direct integration of graphene layer on gold-coated optical fiber. Both linear response to wide range ssDNA concentration from 1 × 10−12 to 10 × 10−6m and low detection limit of 1 × 10−12m are achieved. The resulting hybrid plasmonic sensor shows prospects of highly sensitive, highly integrated, and flexible sensing at fiber-optic length scale.